Se jouer des situations : Usages de mondes « virtuels » en contextes de handicap - Guïoux, Axel; Lasserre, Evelyne (Anthropologica, 2022)
This article is a continuation of ongoing research to understand the uses of online gaming by people with physical disabilities. By emphasizing the epistemic and methodological contributions of online ethnography, it points to the heuristic limits of the traditional distinction between a supposedly real world and that which would be repeated in the virtual. The spe cific use of video games in this example, makes it possible not only to question the virtual-real dichotomy, but also to ques tion the traditional definition of the game which starts from the premise that the rule is distinct from its concrete execution. Analysis of the recreational practices of disabled people also points to the need for attention to modes of bodily appropriation of techno-communication devices. In the end, it is a question of considering video entertainment experiences like "instances of proxy," authorizing the sensitive exploration of worlds that are less disconnected and instead are in constant interaction.